Regional development disparities in Malaysia - Karimi, Mohammad Sharif; Yusop, Zulkornain; Law, Siong Hook (Marsland Press, 2010)
Achieving balanced regional development will remain as one of the key objectives of national development during the development Plans in Malaysia. Therefore this paper analyses regional disparities amongst major states in Malaysia to find out gap and rank of regional development during two development plan (Seventh and Eighth plan). The paper proposes a new methodology that includes TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) and Shannon entropy for first time in terms of ranking in this field. The empirical results indicate that in terms of regional balance, little progress was made in reducing development gaps between regions during two plans and Wilayah Persekutuan Kuala Lumpur was the most developed region in 2000 and 2005. On the other hand, Sabah was the least developed region in same period.